Learning Management in Physical Education Subjects at State High School 2 Bengkulu - Perdima, Feby Elra; Personi, Megi (Universitas Majalengka, 2023)
Investigating learning management in Physical Education classes at State Senior High School 2 Bengkulu is the goal of this study. Given the significance of physical education in shaping students' health and character, it is imperative to comprehend how learning management might impact classroom instruction efficiency. This study aims to examine how State High School 2 Bengkulu's Physical Education classes use learning management techniques and to pinpoint the variables that affect how learning management is implemented in this setting. This research uses a qualitative approach with a case study method. Document analysis, interviews, and observation were used to gather data. The research participants comprised two physical education teachers, sixty-four pupils, and school staff. According to the study's findings, Bengkulu State High School 2's physical education classes still employ learning management strategies that need to be improved in several areas, including formative assessment, student interaction, and the use of technology in the classroom. These elements impact how well students learn physical education in the classroom. Comprehensive examination of study results and their application to learning management principles. The implications of the research findings for bettering learning management strategies in Physical Education courses are also covered. The study's findings lead to the conclusion that some learning management issues in Physical Education courses require improvement. This conclusion offers State Senior High School 2 Bengkulu a foundation for enhancing and developing its instructional strategies. This study's limitations include its short duration and narrow focus on a single school. Formative assessments should be used, technology utilisation should be improved, and student involvement should be raised. Involving additional groups in the learning management development process, such as parents and school committees, is also advised.